Respon Konsumsi Kambing Peranakan Etawa terhadap Pemberian Pakan Komplit Berdasarkan Kadar Pulp Kakao yang Berbeda - Jisril Palayukan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Addressing the need for sustainable goat feed solutions, the utilization of agricultural waste emerges as a viable option. However, the current practice primarily involves transforming cocoa pods into goat feed, neglecting the potential of the discarded cocoa pulp, which contributes to environmental pollution. This study aims to evaluate the consumption patterns of crude protein and crude fiber in corn cobs-based complete feed enriched with varying levels of cocoa pulp, administered to Etawa crossbreed goats. The experiment was structured around a 4x4 Latin Square Design, encompassing four treatments and four periods. The treatments encompassed P0, which comprised complete feed without cocoa pulp; P1 with 5% cocoa pulp; P2 with 10% cocoa pulp, and P3 with 15% cocoa pulp. By employing this design, researchers sought to ascertain the influence of cocoa pulp concentration on consumption patterns. The findings shed light on the average daily consumption of crude protein (in grams per head) for each treatment: P0 recorded 40.52, P1 exhibited 67.95, P2 observed 55.35, and P3 noted 51.75. Furthermore, the daily consumption of crude fiber (in grams per head) across treatments yielded the following results: P0 reported 77.19, P1 registered 135.99, P2 showed 113.97, and P3 demonstrated 94.56. In conclusion, the study demonstrates that incorporating cocoa pulp as a replacement for molasses in corn cobs-based complete feed formulation has no significant impact on the consumption of crude protein or crude fiber. This finding suggests that the integration of cocoa pulp in goat feed formulation is a promising approach that can contribute to sustainable resource management, without adversely affecting goats' dietary patterns.